2021
DOI: 10.1088/1748-3190/abce4c
|View full text |Cite
|
Sign up to set email alerts
|

Can the ground enhance vertical force for inclined stroke plane flapping wing?

Abstract: The numerical investigation of 2D insect wing kinematics in an inclined stroke plane is carried out using an immersed boundary solver. The effect of vortex shedding and dipole jet on the vertical force generation by the flapping wing due to change in the stroke plane angle is investigated in the vicinity of the ground. The results of instantaneous force and vorticity contours reveal the underlying lift enhancement mechanisms for the inclined stroke plane flapping wing. Moreover, they aid in the understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The stroke plane angle was found to change the dipole jet characteristics (Deepthi and Vengadesan 2020) and the jet characteristics were found to explain the vertical force trends in hovering conditions. Further, vertical force enhancement due to the ground effect for intermediate heights could also be explained by the dipole jet patterns (Deepthi and Vengadesan 2021). This calls for understanding the effect of dipole jet on the tandem wing configuration and their role in vertical force enhancement.…”
Section: Introductionmentioning
confidence: 94%
“…The stroke plane angle was found to change the dipole jet characteristics (Deepthi and Vengadesan 2020) and the jet characteristics were found to explain the vertical force trends in hovering conditions. Further, vertical force enhancement due to the ground effect for intermediate heights could also be explained by the dipole jet patterns (Deepthi and Vengadesan 2021). This calls for understanding the effect of dipole jet on the tandem wing configuration and their role in vertical force enhancement.…”
Section: Introductionmentioning
confidence: 94%
“…However, it is important to note that the 'air cushion' underneath the body is created by the downwash from the flapping wings. Different from these effects which is caused by the downwash [50] or happened simultaneously with the vortex wake in inclined stroke plane [48,49], our present work shows that this 'ramming effect' also exists for the insect flapping wing in ground effect when the wing flaps in a horizontal plane without any vortex wake (or downwash).…”
Section: Ramming Effectmentioning
confidence: 46%
“…This effect has been identified as the dominant factor of the ground effect on a flapping bird [47]. Studies on flapping wings with inclined stroke plane angle in ground effect also showed the ramming effect on the wings, where it is also referred as 'cushion effect' [48,49]. This air cushion effect was also found to enhance the lift on the insect body when the fruit fly model hovered above the ground [50].…”
Section: Ramming Effectmentioning
confidence: 95%
“…This low-pressure region acts as a sink flow, drawing fluid between the two vortices. This combination of source flow and sink flow forms a dipole jet that is characteristic of counter-rotating vortices (Drucker & Lauder 2000; Deepthi & Vengadesan 2021). The schematic diagram in figure 10 illustrates the pitch-up motion of the wing and the resulting formation of the dipole jet.…”
Section: Resultsmentioning
confidence: 99%
“…They also observed that pitching near the ground generates a vortex pair instead of a vortex street, increasing the average thrust force. In another study, Deepthi & Vengadesan (2021) showed that an inclined flapping wing-in-ground effect experiences an enhanced vertical force at a stroke plane angle of due to the interaction of the recirculating jet with the wing. However, at other angles, the influence of the ground on the jet is minimal or non-existent, resulting in negligible changes in the force with varying ground height.…”
Section: Introductionmentioning
confidence: 99%